A Parallel Coordinates Visualization for the Uncapaciated Examination Timetabling Problem - Thomas, J. Joshua; Khader, Ahamad Tajudin; Belaton, Bahari (Visual Informatics: Sustaining Research and Innovations, 2011)
The paper describes a new approach, based on visualization, to the uncapacitated examination timetabling problem. This approach involves with a naturally inspired evolutionary technique with parallel coordinates that facilitates exploration of data. By explicitly representing the visualization parameter space, the interface provides an overview of rendering options and enables user to easily explore different processes namely preprocessing, during the processing and post processing of examination schedules. The paper discusses the performance of this method on the Carter set of benchmark problems. This data set is comprised of real-world timetabling problems.